2015
DOI: 10.1186/2055-0928-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Weekly cholecalciferol supplementation results in significant reductions in infection risk among the vitamin D deficient: results from the CIPRIS pilot RCT

Abstract: Background: Observational studies suggest vitamin D deficiency may contribute to the risk of acute infections. We undertook a randomised controlled trial (RCT) of cholecalciferol supplementation as an intervention against acute infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…The pooled summary estimate of six studies [ 35 , 36 , 38 41 ] showed a marginal mean reduction in symptom duration (MD -0.06 days; 95% CI -0.29 to 0.18) in the vitamin D group compared to placebo, which was not statistically significant ( Fig 5 ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The pooled summary estimate of six studies [ 35 , 36 , 38 41 ] showed a marginal mean reduction in symptom duration (MD -0.06 days; 95% CI -0.29 to 0.18) in the vitamin D group compared to placebo, which was not statistically significant ( Fig 5 ).…”
Section: Resultsmentioning
confidence: 98%
“…Five studies [ 35 , 36 , 38 , 39 , 41 ] assessed severity of RTI symptoms on various scales. Definitions applied to assess symptom severity were as follows: the average self-rated score of symptom severity on a scale of 1 to 7 (1 = very mild, 3 = mild, 5 = moderate, 7 = severe) [ 35 ], the sum of seven consecutive daily severity scores [ 36 , 39 ], and the mean severity score on a scale from 1–5 (1 = healthy and 5 = very ill) [ 38 ] and 0–5 (0 = no symptoms and 5 = most severe symptoms) [ 41 ], respectively. The pooled OR of 0.95 (95% CI 0.76 to 1.18) suggests less pronounced severity in the vitamin D group, but this result did not reach statistical significance ( Fig 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simpson et al reported that a protective vitamin D effect (20 000 IU/wk cholecalciferol 17 wk during winter) towards acute infections (respiratory, gastrointestinal, urinary tract, eye, ear, skin, and cold sore infections) could only be observed in the subgroup of healthy adults with initial 25(OH)D levels <40 nmol/L (n = 4 of 34 healthy adults) . No microbiological verification of symptoms was available.…”
Section: Vitamin D Supplementation In Preventing Aris In Healthy Peoplementioning
confidence: 99%
“…Moreover, in three trials with initial 25OHD levels <50 nmol/l [ 54 , 60 , 68 ], the odds ratio of vitamin D effectiveness was 0.55 (95 % CI 0.20–1.55), indicating that initial 25OHD level may also influence vitamin D effectiveness. Notably, Simpson et al [ 67 ] reported that a protective vitamin D effect could only be observed in the subgroup of individuals with initial 25OHD levels <40 nmol/l. In these individuals, vitamin D resulted in a 44 % reduction in infection risk ( P = 0.007).…”
Section: Clinical Associations Of Vitamin D With Acute Airway Infectimentioning
confidence: 99%